Evaluation of the apical leakage of isobutyl cyanoacrylate when used as a root canal sealant. - (:unkn) unknown (My University, 1990)
The sealing properties of isobutyl cyanoacrylate were evaluated in extracted single-rooted human teeth. In the experimental group, instrumented root canals were obturated with isobutyl cyanoacrylate and gutta-percha by using the lateral condensation technique. In the control group instrumented root canals were obturated with gutta-percha only. The penetration of radioactive 131I was evaluated by an autoradiographic technique. No leakage was observed in the experimental group. This study shows that isobutyl cyanoacrylate is a good apical sealant.